2012
DOI: 10.1161/hypertensionaha.112.195115
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase 4 Inhibitor Sitagliptin Protects Endothelial Function in Hypertension Through a Glucagon–Like Peptide 1–Dependent Mechanism

Abstract: Abstract-Sitagliptin, a selective dipeptidyl peptidase 4 inhibitor, inhibits the inactivation and degradation of glucagon like peptide 1 (GLP-1), which is used for the treatment of type 2 diabetes mellitus. However, little is known about the role of GLP-1 in hypertension. This study investigated whether the activation of GLP-1 signaling protects endothelial function in hypertension. Two-week sitagliptin treatment (10 mg/kg per day, oral gavage) improved endotheliumdependent relaxation in renal arteries, restor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
143
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(150 citation statements)
references
References 47 publications
(39 reference statements)
3
143
0
4
Order By: Relevance
“…46 Limei et al reported that DPP-4 inhibitor sitagliptin administered to hypertensive rats spontaneously improved endothelial function by restoring nitric oxide bioavailability. 47 Glorie et al reported that DPP-4 inhibitor vildagliptin attenuated AKI in a rat ischemia-reperfusion model. 20 Although the mechanisms of action of DPP-4 inhibition on ischemic AKI were not clarified in the above-mentioned reports, we clarified for the first time that a GLP-1-mediated antiapoptotic effect contributed to renal protection in a mouse CP-AKI model.…”
Section: Discussionmentioning
confidence: 99%
“…46 Limei et al reported that DPP-4 inhibitor sitagliptin administered to hypertensive rats spontaneously improved endothelial function by restoring nitric oxide bioavailability. 47 Glorie et al reported that DPP-4 inhibitor vildagliptin attenuated AKI in a rat ischemia-reperfusion model. 20 Although the mechanisms of action of DPP-4 inhibition on ischemic AKI were not clarified in the above-mentioned reports, we clarified for the first time that a GLP-1-mediated antiapoptotic effect contributed to renal protection in a mouse CP-AKI model.…”
Section: Discussionmentioning
confidence: 99%
“…DPP-4 inhibitors may improve cardiac outcomes following myocardial infarction via cytoprotective pathways (15). Notably, DPP-4 inhibitors have been demonstrated to exert antiatherogenic effects on improving endothelial function through augmenting GLP-1 activity, and the anti-inflammatory effect of DPP-4 inhibitors has been suggested in preclinical and clinical studies of type 2 diabetes and coronary artery disease (16,17). However, the role of DPP-4 inhibitors in septic inflammation, which may lead to cardiovascular complications, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In support to our study results, Yang et al (2014) [28] have recently demonstrated that DPP4 activity is significantly higher in healthy subjects with higher blood pressure and insulin resistance determinated by HOMA-IR index in apparently healthy Chinese man and woman. Recent experimental and clinical studies suggest that DPP4 inhibition reduces blood pressure [29] although the underlying mechanism remains poorly understood. Currently, there are evidence that DPP4 inhibition leads to increased nitric-oxide (NO) bioavailability but the question whether the it occurs in a direct or indirect pathway indicating the potential role of DPP4 substrates, especially via glucagon-like peptide-1 (GLP-1) receptor [30,31].…”
Section: Discussionmentioning
confidence: 99%